Temporal regulation of ZBTB16 expression by glucocorticoids alters human cortical neurogenesis - Krontira, Anthi C; Cruceanu, Cristiana; Kyrousi, Christina; Dony, Leander; Link, Marie-Helen; Kappelmann, Nils; Pöhlchen, Dorothee; Roeh, Simone; Sportelli, Vincenza; Wölfel, Barbara (bioRxiv, 2022)
Glucocorticoids are important for proper organ maturation1. Increased exposure to these hormones during pregnancy, as a result of commonly prescribed synthetic glucocorticoids such as dexamethasone in preterm births2, has been associated with lasting effects on the offspring, including on neurodevelopment and neuropsychiatric disease risk3. While the consequences of glucocorticoid excess in term and especially adult brain have been extensively studied, mainly in rodents4, studies on their effects during early human cortical development are absent. Here we use human cerebral organoids and mice to study cell-type specific effects of glucocorticoids on neurogenic processes. We show that glucocorticoid administration during neurogenesis alters the cellular architecture of the developing cortex by increasing a specific type of gyrencephalic species-enriched basal progenitors that co-express PAX6 and EOMES. This effect is mediated via the glucocorticoid-responsive transcription factor ZBTB16 as shown with overexpression, genetic knock-down and reporter assays experiments in organoids and embryonic mouse models and leads to increased production of deep-layer neurons. A phenome-wide mendelian randomization analysis of a genetic intronic enhancer variant that moderates glucocorticoid-induced ZBTB16 levels, as shown with enhancer assays and enhancer-editing in organoids, reveals potential causal relationships with increased educational attainment as well as neuroimaging phenotypes in adults. In this study we provide a cellular and molecular pathway for the effects of glucocorticoids on human neurogenesis that potentially explains postnatal phenotypes and may be used to refine treatment guidelines.